Pengembangan Media Pola Perlahan pada Materi Perkalian Siswa SD Kelas II - Aswarliansyah Aswarliansyah; Riduan Febriandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine the validity, practicality and effectiveness of the slowly developed media. This research is a development research written by Sugiyono, but in this study adapted 9 steps, namely 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, 6) Product trial, 7 ) Product Revision, 8) Usage Trial, 9) Product Revision. Collecting data through validation sheets, practicality sheets and question instruments. Expert validation analysis was carried out using the AIken's V formula and calculated the average score of the three validators. The results of the validation analysis were obtained at 0.886 with high criteria. While the results of the analysis of practicality obtained by 91.5%. The effectiveness of using slow pattern media was analyzed using the z-test. the value of Z_count (2.95) > Z_table (1.64), then Ha is accepted and Ho is rejected. The slowly developed pattern media meets the criteria of being valid, practical and suitable for use in learning mathematics with multiplication material. Keywords: Development, Media, Pattern Slowly